Pharmacognostical, phytochemical, and in vitro bioassay studies of Osbeckia stellata Buch-ham. leaves - Bordoloi, Chayanika; Bora, Nilutpal Sharma; Laloo, Damiki (Journal of Applied Pharmaceutical Research, 2025)
Background: Osbeckia stellata (Os) is a medicinally significant herb that is consumed for the treatment of various diseases, including skin diseases, diabetes, diarrhea, cancer, asthma, arthritis, dysentery, leukoderma, hypertension, jaundice, malaria, rheumatism, spondylitis, and tuberculosis, as well as inflammation and wound healing. Methodology: This study standardizes the plant of Os by accepted practices. Os leaves have been examined physicochemically, phytochemically, microscopically, and morphologically. Extracts were reviewed for both qualitative and quantitative phytochemical examination, and in vitro bioassays were also evaluated. Results: Diagnostic traits, such as xylem arteries, trichomes with cover, and anomocytic stomata, were identified in the histological study. Nutritional profiling revealed fiber content (48.1 ± 0.99 mg/100 g). Heavy metal analysis revealed that Pb, Hg, Sn, Sb, Cd, Cu, and As were within the permissible limits. Pesticide residues were verified with ICP-MS analysis. The in vitro antioxidant studies of different extracts show IC₅₀ values 1003.35±0.23, 152.11±0.1, 192.12±0.14, 111.79±0.06, and 982.49±0.31 (μg/ml) as compared to standard 130.54±0.03 and 330.86±0.09 (μg/ml). Antimicrobial assay studies show the Zone of Inhibition by different extracts is 26.00 ± 1.20, 17.00 ± 0.60, 18.66 ± 0.58, 22.33 ± 1.52, 6.33 ± 0.58 (mm) as compared to the standard 38.00 ± 1.00, 35.00 ± 1.35, 22.00 ± 1.00, 41.00 ± 1.00, 30.66 ± 1.54(mm). Discussion: The methanol extract of Os has total phenols and total tannins of 120.04±5.97 and 123.0±1.52 (mg/g TAE), respectively, which is high in quantity and is reported to possess high antimicrobial and antioxidant properties.  Conclusion: This study concludes that the quality control parameters for Os are essential for promoting its use in pharmaceutical applications.